To Achieve Carbon Neutrality Targets in Pakistan: New Insights of Information and Communication Technology and Economic Globalization - Iqbal, Kashif; Hassan, Syed Tauseef; Wang, Yichu; Shah, Muhammad Haroon; Syed, Madeeha; Khurshaid, Khurshaid (Frontiers in Environmental Science, 2022)
In recent years, information and communication technology (ICT) are used in every sphere of life, from business to services, education to culture, infrastructure to transportation, and art to entertainment. The current study focuses to assess the impact of ICT, economic growth, and economic globalization on CO2 emission in the context of Pakistan. For empirical estimation, the current study applied an innovative methodological approach called Generalized Least-Square (GLM) and ROBUSTLS technique for the year 1990 to 2019. The key finding of the finding of this study shows that economic growth (GDP) has a positive and significant effect on CO2 emission, which confirm that economic growth (GDP) accelerates the rate of emission, while the finding of the study also reveals that information and communication technology usage (more specifically ICT-internet and ICT-mobile subscription) have a negative but significant effect on CO2 emission, which confirms that the usage of ICT (more specifically ICT-internet and ICT-mobile subscription) doesn’t contribute positively to CO2 emission. Furthermore, the coefficient of economic globalization has a positive and significant effect on the CO2 emission, which confirms that economic globalization accelerates the CO2 emission in the country. Also, the results indicate that information and communication technology usage (more specifically ICT-internet and ICT-mobile subscription) could boost economic growth and mitigate climate change. Based on the policy perspective, the government of Pakistan needs to strategically focus on the ICT sector and more specifically on technological innovations to promote sustainable economic growth in the country.